Maternal and infant correlates of maternal feeding beliefs and practices in a multi-ethnic Asian population: The GUSTO (Growing Up in Singapore Towards healthy Outcomes) study - Quah P.L. (Cambridge University Press, 2018)
Public Health Nutrition